A new species of Yola Gozis, 1886 from the Western Cape of South Africa (Coleoptera: Dytiscidae: Bidessini) - Bilton, David T. (Zootaxa, 2015)
Yola matsikammae sp. nov. is described from the Matsikammaberg, an inselberg on the northern edge of the fynbos biome of the Western Cape, South Africa. A key is provided to separate the new species from other southern African members of the Yola bicarinata group. Y. matsikammae sp. nov. bears a superficial resemblance to Sharphydrus species, particularly Sharphydrus brincki Bilton, 2013 with which it was found to co-occur. Comparative notes to separate these taxa are also included.